Business, industry and higher education collaboration: a panacea in developing professional work-ready graduates - Rufai, Ahmed Umar; Bakar, Ab Rahim; Mat Rashid, Abdullah (Richtmann Publishing, 2015)
The purpose of this paper is to explore how institutions of higher learning, industries and businesses work together to accomplish mutual goals, intended to help shape and inform up-to-date curriculum and course design. The aim was to improve mutual understanding and exchange of ideas between the Education and business sectors that can lead to produce professional work-ready graduates. The research method was essentially qualitative case-study design method (Yin, 2003), was used. The researcher collected documents, conducted semi-structured interviews and recorded observations at the selected multinational companies and recognized institutions of higher learning. The emergent themes from the data, in form of field notes, interview scripts, audio recordings and information from documents, representing the views of both Educationists and Industrialists were analyzed. The four emergent themes as characterized by the participants views on collaborative efforts between business and Education were identified as; cooperative study programme, technical support and programme delivery, representation in the institution governing council and collaboration through shared facilities. The study represent a means of contributing quality in teaching and learning graduate employability skills, that is vital in the survival and challenge to industry to succeed in an increasingly competitive world market. This paper attempts to provide new ways of thinking as well as formal flexible commitments from business and Education in forming partnership, that enable both sectors share the needs, problems, issues, strengths and weakness of in training professional work-ready graduates.